Energy migration processes in phosphate nanocrystals: size and dimensionality dependence: Низкотемпературная оптическая спектроскопия - Kononets, N.V.; Seminko, V.V.; Maksimchuk, P.O.; Bespalova, I.I.; Klochkov, V.K.; Malyukin, Yu.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
Peculiarities of electronic excitation energy migration in phosphate nanocrystals with three-dimensional (EuPO4) and one-dimensional (EuP3O9) arrangement of regular ions under variation of concentration of both energy traps (Nd3+ ions) and scattering centres (La3+ ions) are discussed in the paper. Processes of energy migration in both EuPO4 and EuP3O9 nanocrystals are phonon-assisted ones due to absence of resonance between energy levels of adjacent Eu3+ ions. The distance of energy migration for both EuPO4 and EuP3O9 nanocrystalswas found to be equal to tens of nanometres, however, for EuPO4 nanocrystals energy migration leads to stronger quenching of Eu3+ luminescence. For 10 nm EuPO4 nanocrystals sufficient hampering of energy migration isobserved due to the depletion of the low-energy phonon spectrum as a result of the phonon confinement effect.